Requirements for the exercise of the labor judge’s exceptional power to incorporate evidence ex officio - Carrasco Cabezas, Francisco (2021)
The Peruvian procedural rules not only give the labor judge the power to act on evidence ex officio, but also invoke him to exercise such power in his capacity as the absolute director of the process. However, this is only call upon in certain cases where his intervention is essential and provided that certain requirements are met. In this article we will try to explain clearly in which cases the Judge must intercede in the process of submitting evidence and what are the requirements for him to do so.